Application of Small Angle X-ray Scattering (SAXS) for Differentiation between Normal and Cancerous Breast Tissue (International Journal of Medical Sciences, 2005)
Introduction: Small angle, between 3° and 10°, X ray scattering is predominantly coherent giving rise to diffraction effects that can be observed as constructive and destructive interferences. These interferences carry information about the molecular structure of the tissue and hence can be used to identify changes that occur due to cancer. Method: In this study an energy dispersive X-ray diffraction method was used. The optimum scattering angle, determined from a series of measurements on adipose breast tissue at several angles from 4 to 7.3 degrees, was found to be 6.5°. Once optimized the system was used to measure the diffraction profiles (corrected scattered intensity versus momentum transfer) of a total of 99 breast tissue samples. The samples were both normal and tumour samples. Results: Adipose tissue showed a sharp, high intensity peak at low momentum transfer values of approximately 1.1nm-1. Adipose tissue, mixed tissue (adipose & fibroglandular) and tumor have peaks at different values of momentum transfer that can be used to identify the tissue. Benign and malignant breast tissues can also be differentiated by both peak positions and peak heights. It was also observed that the results were reproducible even after the tissue had been preserved at liquid nitrogen temperatures. Conclusion: We were able to differentiate between normal, benign and malignant breast tissues by using energy dispersive small angle x-ray scattering.